2009
DOI: 10.1074/jbc.m109.014639
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transforming Growth Factor-β-dependent Cyclooxygenase-2 Expression in Fibroblasts

Abstract: Abnormal transforming growth factor-␤ (TGF-␤) signaling is a critical contributor to the pathogenesis of various human diseases ranging from tissue fibrosis to tumor formation. Excessive TGF-␤ signaling stimulates fibrotic responses. Recent research has focused in the main on the antiproliferative effects of TGF-␤ in fibroblasts, and it is presently understood that TGF-␤-stimulated cyclooxygenase-2 (COX-2) induction in fibroblasts is essential for antifibroproliferative effects of TGF-␤. Both TGF-␤ and COX-2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
1
17
1
1
Order By: Relevance
“…Previous reports have demonstrated that TGF-β1 increases COX-2 expression and PGE 2 synthesis in fibroblasts over short periods (2–24 h) [24][26]. These reports agree with our results, since we observed increased COX-2 induced by TGF-β1 at 4 and 24 h in control fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports have demonstrated that TGF-β1 increases COX-2 expression and PGE 2 synthesis in fibroblasts over short periods (2–24 h) [24][26]. These reports agree with our results, since we observed increased COX-2 induced by TGF-β1 at 4 and 24 h in control fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…TGF-b increases PGE 2 production in rat astrocytes and neurons (29). Although we (8,14,28) demonstrated that TGF-b may modulate immune response by regulating PG production, little information is available on the molecular mechanisms of TGF-b-induced COX-2 induction, as also pointed out by Matsumura et al (30). We (8,28) observed previously that IL-4 inhibits PG production in HK cells stimulated with TGF-b.…”
mentioning
confidence: 82%
“…The colocalization finding indicates that COX-2 produced by the infiltrating inflammatory cells at the wound site could induce TGF Beta-1 synthesis and production by the same cells through autocrine mechanism or the nearby cells through a paracrine mechanism or both. Paracrine/autocrine signalling between COX-2 and TGF Betahas been extensively studied in several in vitro models [71] and this COX-2 and TGF Beta-1 interregulation was shown in fibroblast [72], in macrophages and intestinal epithelial lining [73,74], in bronchial epithelium [75] in lung fibroblasts [76] and in keratinocytes [77]. Paracrine/autocrine regulation between COX-2 and TGF Beta and other growth factor has been a hot area of research in oncology as this inter-regulation was proposed to play a critical role in cancer invasion and metastasis [74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%